2018
DOI: 10.1055/s-0038-1657771
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Aortic Aneurysm: Evolving Controversies and Uncertainties

Abstract: Abdominal aortic aneurysm (AAA) is defined as a permanent dilatation of the abdominal aorta that exceeds 3 cm. Most AAAs arise in the portion of abdominal aorta distal to the renal arteries and are defined as infrarenal. Most AAAs are totally asymptomatic until catastrophic rupture. The strongest predictor of AAA rupture is the diameter. Surgery is indicated to prevent rupture when the risk of rupture exceeds the risk of surgery. In this review, we aim to analyze this disease comprehensively, starting from an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
17

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 264 publications
(238 reference statements)
2
36
0
17
Order By: Relevance
“…Male sex is considered one of the most influential risk factors for AAA with advanced age. It was reported that the incidence was common in men over the age of 65 years (Carino, Sarac, Ziganshin, & Elefteriades, 2018;Lederle et al, 1997) Screening ultrasonography is essential to assess AA. It is a useful diagnostic imaging modality since it is safe, simple, inexpensive, and accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Male sex is considered one of the most influential risk factors for AAA with advanced age. It was reported that the incidence was common in men over the age of 65 years (Carino, Sarac, Ziganshin, & Elefteriades, 2018;Lederle et al, 1997) Screening ultrasonography is essential to assess AA. It is a useful diagnostic imaging modality since it is safe, simple, inexpensive, and accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Nakon objavljenih rezultata iz četiri velike studije (Čičester studija, Velika Britanija; Zapadnoaustralijska studija u Pertu, Australija; Viborg studija, Danska; MASS multicentrična skrining studija -Oksford, Portsmut, Vinčester i Sau-thempton: Velika Britanija) u Velikoj Bri-taniji je 2009. godine uveden nacionalni skrining program za AAA koji je pokazao značajan benefit za muškarce starije od 65 godina koji su uključeni u skrining i tako se smanjio procenat smrti povezanih sa AAA. Na istim dokazima, pre više godina, skrining programi su uvedeni u SAD i Švedskoj, s tim što su u SAD-u pozivani muškarci stariji od 65 godina sa pozitivnom anamnezom o pušenju, ali i žene sa pozitivnom porodičnom anamnezom za AAA [6]. Osim muškog pola i starosti, drugi važni faktori rizika koji se izdvajaju u čak više od ⅔ pacijenata su hipertenzija, povišene vrednosti masnoća u krvi, fizička neaktivnost, pušenje i hiperglikemija.…”
Section: Diskusijaunclassified
“…Prilikom rupture AAA karakterističan je trijas: jak abdominalni bol ili bol u donjem delu leđa, pulzatilna masa u abdomenu/odsustvo pulsa nad femoralnim arterijama i hipotenzija. [5] AAA se najčešće otkriva kao slučajan nalaz pri radiološkim pretragama u vidu ultrazvuka ili multislajsne kompjuterizovane tomografije (MDCT). Izuzetno, može se videti i pri nativnoj radiografiji abdomena ukoliko su zidovi aneurizme izuzetno kalcifikovani [6].…”
unclassified
See 2 more Smart Citations